1989
DOI: 10.1111/j.1600-051x.1989.tb01648.x
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil chemotactic behaviour in patients with early‐onset forms of periodontitis

Abstract: Despite some reports to the contrary, it is generally assumed that early-onset forms of periodontal disease (including both juvenile and rapidly progressive periodontitis) are associated with a defect in neutrophil (PMN) chemotactic behaviour. Using the Boyden chamber technique and N-formyl-methionyl-leucylphenylalanine (FMLP) to assess locomotion by the leading front method, we have failed to show any evidence for such depressed PMN locomotion. Indeed, when PMN chemotaxis and chemokinesis are considered in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 19 publications
2
26
0
Order By: Relevance
“…For instance, in US-based studies, approximately 60%-70% of LAP patients exhibit a decreased neutrophil chemotaxis trait (Van Dyke et al 1985Daniel et al 1993). This is far lower in northern Europe and Finland (Saxen 1980;Kinane et al 1989). The finding is best illustrated in African-American study populations.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in US-based studies, approximately 60%-70% of LAP patients exhibit a decreased neutrophil chemotaxis trait (Van Dyke et al 1985Daniel et al 1993). This is far lower in northern Europe and Finland (Saxen 1980;Kinane et al 1989). The finding is best illustrated in African-American study populations.…”
Section: Introductionmentioning
confidence: 99%
“…In several diseases, leucotactic abnormalities have been found, i.e., in the Chediak-Higashi Syndrome (Clark & Kimball 1971), in patients with rheumatoid arthritis (Mowat & Braun 1972) or diabetes mellitus (Mowat & Baum 1971, Kjersem et al 1988, and in Crohn's disease (D'Amelio et al 1985). These authors reported mainly about a reduced chemotactic function in LEOP patients, but others have discussed an enhanced chemotactic response of peripheral blood PMN in these periodontitis forms (Kinane et al 1989, Repo et al 1990). Chemotaxis disorders of peripheral blood PMN have been described in some forms of early onset periodontitis (EOP) including localised early onset periodontitis (LEOP), generalised early onset periodontitis (GEOP), and pre-pubertal periodontitis (Page & Schroeder 1982, Van Dyke et al 1981, Van Dyke et al 1985, 1987, Coles et al 1989, Daniel et al 1993.…”
mentioning
confidence: 99%
“…decrease Chemotaxis of healthy neutrophils towards chemoattractants, were recently confirmed.2526 These observations have been expanded to show that treatment of healthy neutrophils with LJP sera decreases the number of FMLP receptors on the neutrophil surface.4142 Furthermore, pretreatment of LJP sera with anti-TNF and anti-IL-1 antibodies partially neutralizes the ability of LJP sera to decrease Chemotaxis and the number of FMLP receptors on healthy neutrophils.4142 The changes induced by LJP sera are specific, sustained and cannot be reversed by placing LJP serum-treated neutrophils in healthy serum. In this regard, healthy neutrophils treated with LJP sera function similarly to LJP neutrophils.…”
mentioning
confidence: 85%
“…4-6-22-24 In some cases, a 10% to 20% increased chemotactic response has also been observed. [25][26] Although it is generally agreed that neutrophils from a majority of LJP patients exhibit decreased Chemotaxis, the mechanisms responsible for this altered neutrophil function are under considerable debate. To date, there are two plausible explanations for the observed decreased neutrophil Chemotaxis in LJP: 1) neutrophils are intrinsically defective; or 2) extrinsic factors in the sera of LJP patients alter neutrophil functions.…”
Section: Altered Neutrophil Function Inmentioning
confidence: 99%